PRECISION.array: An R Package for Benchmarking microRNA Array Data Normalization in the Context of Sample Classification - Huang, Huei-Chung; Wu, Yilin; Yang, Qihang; Qin, Li-Xuan (Frontiers in Genetics, 2022)
We present a new R package PRECISION.array for assessing the performance of data normalization methods in connection with methods for sample classification. It includes two microRNA microarray data sets for the same set of tumor samples, a re-sampling-based algorithm for simulating additional paired data sets under various designs of sample-to-array assignment and levels of signal-to-noise ratios, and a collection of numerical and graphical tools for method performance assessment. The package allows users to specify their own methods for normalization and classification, in addition to its implementation of three methods for training data normalization, seven methods for test data normalization, seven methods for classifier training, and two methods for classifier validation. It enables an objective and systemic evaluation of the operating characteristics of normalization methods and classification methods in microRNA microarrays. To our knowledge, this is the first such tool available. The R package can be downloaded freely at https://github.com/LXQin/PRECISION.array.